(untitled) (Health Renaissance, 2017)
Third molar surgery is one of the major events carried out world-wide in a maxillofacial clinic. Preoperative assessment of surgical difficulty is fundamental to planning of extraction of impacted third molars. Various models for this assessment have been proposed but none is universally applicable. Although several studies have identified a plethora of factors associated with extraction difficulty, as measured via a wide variety of proxy variables, still, there are conflicting reports and wide variations of the enumerated factors. Adding to the existing knowledge, through this communication we would like to suggest that tooth impaction should also be considered as a variable of difficult third molar extraction. It requires both surgical expertise and added operating time thus affecting difficulty index. So we suggest tooth impaction should be considered as a difficulty assessment tool and studies be carried out to produce an evidence based database. Health Renaissance 2015;13(2): 180-182